Interleukin 10 Plays an Important Role in Neonatal Rats with Hypoxic-Ischemia Associated with B-Cell Lymphoma 2 and Endoplasmic Reticulum Protein 29. (2nd June 2021) - Bai, Xue; Xiong, Liu-Lin; Fang, Chang-Le; Zhou, Hao-Li; Xue, Lu-Lu; Hu, Yue; Xia, Qing-Jie; Liu, Jia; Zhang, Jun-Yan; Wang, Ting-Hua; Yang, Si-Jin
Abstract : Interleukin 10 (IL-10) is a synthetic inhibitor of human cytokines with immunomodulatory and anti-inflammatory effects. This study was designed to investigate the expression variation of IL-10 in the multiple sites including cortex, hippocampus, and lung tissues of neonatal hypoxic-ischemic (HI) rats and explore the crucial role of IL-10 in alleviating HI brain damage. In this study, neonatal Sprague-Dawley rats were subjected to the right common carotid artery ligation, followed by 2 h of hypoxia. The expression of IL-10 in the cortex, hippocampus, and lung tissues was measured with immunohistochemistry, real-time quantitative polymerase chain reaction (RT-qPCR), and western blot (WB). Immunofluorescence double staining was performed to observe the localization of IL-10 in neurons and astrocytes. Moreover, not-targeting and targeting IL-10 siRNA lentivirus vectors were injected into the rats of the negative control (NC) and IL-10 group, respectively, and the mRNA levels of B-cell lymphoma 2 (Bcl-2) and endoplasmic reticulum protein 29 (ERp29) were detected by RT-qPCR following IL-10 silence. The results demonstrated that the IL-10 expression was markedly increased after HI and IL-10 were colocalized with neurons and astrocytes which were badly injured by HI insult. In addition, Bcl-2 and ERp29 were remarkably decreased following IL-10 mRNA interference compared with the NC group. Our findings revealed that IL-10 exerted its antiapoptotic and neuroprotective effects by regulating the expression of Bcl-2 and ERp29, indicating that IL-10 may be a promising molecule target for HIE treatment.